Effect of vermicompost and fertility levels on growth, yield, nutrient uptake and net returns in pearl millet (Pennisetum glaucum) - CHOUDHARY, RAKESH; YADAV, L R; SHIVRAN, A C; PARIHAR, S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2010 in semi- arid climate of Rajasthan to asses the effect of vermicompost and fertility levels on the pearl millet. Application of vermicompost @ 6 tonnes/ha significantly improved the growth and yield attributes and yields of the pearl millet. Application of vermicompost @ 6 tonnes/ha increased the grain yield of pearl millet by 51.4, 20.1 and 7.3% and stover yield by 42.4, 19.3 and 6.3 percent respectively over control, 2 and 4 tonnes/ha vermicompost, respectively. Application of vermicompost @ 6 tonnes/ha recorded significantly higher N content in grain and stover indicating an increase of 10.4 and 16.3 over control, 13.5 and 8.4 over 2 tonnes/ha and 16.6 and 3.2 percent over 4 tonnes/ha, respectively. Phosphorus content in grain and stover were significantly higher by 11.6 and 13.7% over control. Application of 6 tonnes/ha of vermicompost significantly increased N and P uptake in pearl millet. The highest net return (` 11 785) was obtained with vermicompost @ 2 tonnes/ha and minimum with 6 tonnes/ha vermicompost. Application of 100% RDF significantly increased nutrient content, nutrient uptake and net return (` 13 798/ha) and proved significantly superior to all the lower levels of fertility.